Risk Analysis of a Construction Project Considering Seismic Hazards using Primavera A Review - Shivam Mishra; M.P. Verma (International Journal of Scientific Research in Civil Engineering, 2021)
Implementation of construction project needs a proper planning and scheduling is of vital importance for the project to be executed and run smoothly. A best schedule has to be prepared in such a way that meets the primary objectives of the total project. Those essential destinations are to make a quality venture, finished on time, inside spending plan, and in a sheltered workplace. Consequently in this investigation a progressing development venture is taken and the execution of the undertaking is contrasted and the calendar with the assistance of Primavera. In this paper presenting review of literatures related to utilization of management tool
Keywords: Primavera P6.; Gantt Chart; Time-cost Comparison; Cpm Network; Resource Allocation; Project Scheduling; Seismic Hazard